Identification of Grass Weed Seedlings Commonly Found in Florida Sugarcane: A Quick Reference Guide - Dennis C. Odero; Matthew VanWeelden; Christian Kammerer (EDIS)
This article describes proper identification of grass weed seedlings associated with sugarcane in Florida to assist growers with selecting effective control measures. Written by Calvin Odero, Matthew VanWeelden, and Christian Kammerer, and published by the UF/IFAS Agronomy Department, May 2023.